Preparation method of high-orientation hydrophobic oxide antireflection film for diamond infrared window
By preparing a high-oriented hydrophobic oxide resistant film on the diamond infrared window, the problem of low transmittance in the diamond infrared window is solved, and the combination of high transmittance and hydrophobic characteristics is achieved, and its optical performance in the infrared band is improved.
Patent Information
- Application Number
- CN202411567767.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-05
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-11-05
AI Technical Summary
The actual transmittance of diamond infrared windows is affected by the preparation process and surface roughness, and it is difficult to reach 70% of the theoretical transmittance, which seriously restricts its application in the field of optical.
Using a high-oriented oxide target, an urgency film with hydrophobic properties and high-oriented properties is prepared on the diamond surface through magnetron sputtering technology, and the temperature is regulated to control the growth rate of the urgency film to form a multi-layer high-oriented oxide film.
The high transmittance and hydrophobic properties of diamond infrared window are achieved, which effectively reduces water erosion and is conducive to cleaning of the surface, and improves the optical performance of diamond in the infrared band.
Smart Images

Figure CN119433476A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of optical film preparation, and specifically relates to a method for preparing a highly oriented anti-reflection film with slightly hydrophobic properties for use in diamond infrared windows. The invention is characterized in that optical anti-reflection in the diamond mid-infrared band and a surface with hydrophobic properties are achieved. Background Art
[0002] Infrared windows are optical windows that can transmit ultraviolet rays, visible light, and infrared rays. With the development of the times, the application scope of infrared windows has gradually developed from infrared imaging systems, infrared thermometers, night vision devices, etc. to CO2 lasers, energy transmission windows, and high-Mach aircraft infrared imaging systems, etc., which puts higher requirements on infrared window materials, that is, they need to have properties of high temperature resistance, high radiation resistance, high strength, broadband and high transmittance. Diamond, as the hardest substance on earth, has gradually become an irreplaceable material in the field of infrared windows due to its excellent thermal, optical and good chemical stability. The transmission range of diamond covers X-ray, ultraviolet, visible, infrared, and even microwave bands. The transmittance of infrared and microwave bands can reach up to 71%, and due to the low atomic number, tight covalent bonds and cubic structure of atomic combination, it has high strength, high thermal conductivity and durability. At present, the size of artificially synthesized optical-grade single crystals has reached 1-4 inches, and the size of polycrystalline has reached 2-8 inches, which provides a basis for the application of diamond. But on the other hand, the theoretical transmittance of diamond is only 71%, while the actual transmittance is affected by the preparation process and surface roughness, so that it often does not reach 70%, which seriously restricts the application of diamond in the optical field. Therefore, solving the optical transmittance of diamond has become the most critical issue. In order to meet the application of diamond in the long-wave infrared band, it is often necessary to coat an anti-reflection film. According to the anti-reflection mechanism of infrared light, the refractive index matching the diamond material is about 1.55. At present, the commonly used anti-reflection films are mainly oxides such as HfO2 and Y2O3 prepared by magnetron sputtering and other schemes. They have fine grains, uniform density, low roughness and obvious orientation, which can significantly improve the surface protection ability of diamond and achieve high transmittance of diamond film. The structure of the oxide anti-reflection film is greatly affected by deposition factors (deposition temperature, oxygen partial pressure, cavity pressure, sputtering power, DC bias), deep processing (heat treatment) and surface modification. At present, the anti-reflection film is mainly obtained by using metal target materials and adding oxygen, presenting a film system structure with multiple crystal phases coexisting. It is generally believed that cubic oxides have a higher refractive index and a lower antireflection film thickness, but the antireflection efficiency is relatively poor. The refractive index of monoclinic oxides is more matched and it is easier to improve the antireflection performance, but the grain size is larger and the lattice strain is greater. At the same time, there will be a phenomenon of competitive growth between different crystal structures. Therefore, the performance of multiphase oxide antireflection films is affected by uniformity. Different regions have different crystal types and contents, which leads to challenges in the uniformity of antireflection performance. Summary of the invention
[0003] In order to solve the above problems, the present invention provides a method for growing a highly oriented antireflection film on a diamond infrared window. In the initial stage, the diamond film is double-sided polished to a surface roughness of less than 1 nm to reduce the scattering of infrared light. A highly oriented oxide target is used and the temperature is regulated to prepare a highly oriented antireflection film having hydrophobic properties on the diamond surface by sputtering. On the one hand, highly oriented thin film materials are conducive to obtaining uniform antireflection performance, and it is easy to form a laminated structure by controlling the temperature to balance the sputtering rate and antireflection performance. On the other hand, the hydrophobic property is conducive to the cleaning of the entire window.
[0004] The specific technical solutions of the present invention are as follows:
[0005] A method for preparing a highly oriented hydrophobic oxide antireflection film for a diamond infrared window, wherein the growth rate of the antireflection film is regulated by regulating the temperature, thereby preparing a multilayer highly oriented oxide film on the diamond surface, and specifically comprising the following steps:
[0006] Step 1: Diamond surface precision polishing
[0007] Stick the diamond film on an automatic polishing machine and polish the diamond with a polishing disk until the diamond surface roughness is less than 1nm. Repeat the above steps and perform the same polishing treatment on the other side of the diamond film.
[0008] Step 2: Acid boiling treatment of diamond surface
[0009] The polished diamond film was acid-boiled to remove the metal debris and non-diamond phase remaining on the surface of the diamond film, and then ultrasonically cleaned in acetone, ethanol, and deionized water in sequence, and then dried;
[0010] Step 3: Magnetron sputtering process
[0011] The oxide target was mounted on the RF target, and then the cleaned diamond film was placed in the magnetron sputtering chamber, and the magnetron sputtering chamber was evacuated to a pressure of 1×10 -4 Pa~9×10 -4 Pa, introduce sputtering gas Ar, adjust the gas pressure to 1-3 Pa, adjust the substrate temperature between 25℃ and 1500℃, and the sample stage speed is 3-15rpm. The sputtering thickness is given by the formula d=λ 介 / 4 is determined to obtain the best anti-reflection effect, where λ 介 It is the wavelength of light that needs to be transmitted in the anti-reflection coating.
[0012] At this point, the preparation of a highly oriented antireflection film on the surface of the diamond film has been achieved, and when the contact angle of the sample was subsequently measured, it was found that the sample had a slightly hydrophobic property, which can effectively reduce water erosion and is conducive to cleaning the surface.
[0013] In the above preparation method, in the step one, the polishing process is carried out using an automatic polishing machine, the polishing disk speed can reach 2850r / min, the high-precision mechanical slider drives the grinding head to slide up and down, the front and rear electrode drive drives the grinding head to do reciprocating feed motion, the front and rear speeds are adjusted according to actual needs, and mechanical pressure is provided to make the diamond and the grinding disk frictionally grind. The adjustable pressure range of the automatic grinder is 100~1700N, the front and rear movement of the grinding head is 0~40mm, the grinding monitoring accuracy is 0.02mm, and the grinding flatness is ≤0.02mm.
[0014] In the above preparation method, in the step 2, the acid boiling is preferably carried out using a mixed acid of concentrated sulfuric acid and concentrated nitric acid in a volume ratio of 1:1, heated to boiling in an electric furnace, and the acid boiling time is 30 minutes to 1 hour, wherein the concentration of concentrated sulfuric acid is 70% to 98%, and the concentration of concentrated nitric acid is 65% to 68%.
[0015] In the above preparation method, in step 2, the amounts of acetone, ethanol and deionized water used are all 100-200 ml, the frequency of the ultrasonic machine used is 40 kHz, the ultrasonic time is 30 min, and then the sample is taken out and the surface of the sample is blown dry with nitrogen.
[0016] In the above preparation method, in step three, the oxide composite target material used has a highly oriented crystal structure, and the target material is one or a combination of hafnium oxide, yttrium oxide, erbium oxide, and aluminum oxide.
[0017] In the above preparation method, in step three, silicon or sapphire or other materials are used as substrates to conduct experiments on the hydrophilic and hydrophobic properties of the thin film.
[0018] In the above preparation method, in step 3, since the film sputtering rate and crystal quality are approximately linearly related to the substrate temperature, and the film sputtering rate decreases with the increase of temperature while the optical performance is improved, in order to quickly reach the required thickness and ensure the optical performance of the film, the antireflection film is prepared in a fast and slow manner, that is, low temperature and high temperature are carried out alternately: sputtering at 25-400°C for 30min-1h, sputtering at 500-1500°C for 30min-1h, and sputtering at 500-1500°C for 30min-1h, and the two are carried out alternately until the sputtering thickness reaches d=λ 介 / 4, which can ensure both the growth rate and the high orientation characteristics of the anti-reflection film.
[0019] Beneficial effects:
[0020] 1. Using highly oriented oxide composite targets to prepare highly oriented antireflection films can avoid the appearance of multiple crystal phases in the antireflection film structure;
[0021] 2. The growth rate of the anti-reflection film is regulated by adjusting the temperature. The coating method of alternating low temperature and high temperature can not only increase the growth rate of the anti-reflection film, but also ensure the high orientation characteristics of the anti-reflection film;
[0022] 3. The prepared antireflection film has a slightly hydrophobic property, which can effectively reduce water erosion and is conducive to cleaning the surface;
[0023] 4. The entire process is carried out using a magnetron sputtering device, the synthesis process has good process continuity and is simple. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 This is the XRD measurement diagram of highly oriented oxide film.
[0025] Figure 2 Schematic diagram of the stacked antireflection film.
[0026] Figure 3 It is the contact angle characteristics before and after coating.
[0027] Figure 4 This is the infrared transmittance spectrum of the sample before and after coating. DETAILED DESCRIPTION
[0028] The technical solution of the present invention is further described below in conjunction with specific examples.
[0029] Example 1
[0030] Silicon wafers were selected to test the hydrophilic and hydrophobic properties of the film. The silicon wafers were placed in acetone, ethanol, and deionized water for ultrasonic cleaning in turn. The frequency of the ultrasonic machine was 40kHz and the ultrasonic time was 5 to 30 minutes. The sample was then taken out and the surface of the sample was blown dry with nitrogen. The sample was then placed in a magnetron sputtering chamber. The sputtering conditions were an Ar flow rate of 30 to 100 sccm, a sputtering pressure of 1 to 3 Pa, a temperature of 100°C to 1500°C, and a sample stage speed of 3 to 15 rpm. The sputtering thickness is determined according to the formula d = λ medium / 4. In this way, a highly oriented anti-reflection film is obtained. Figure 1 The XRD measurement diagram of the oxide film on the Si substrate shows that the film is highly oriented. Figure 3 Shown are the contact angle characteristics of the prepared oxide film, indicating that the film exhibits slightly hydrophobic properties.
[0031] Example 2
[0032] The diamond is glued to the automatic polishing machine, the polishing disc speed is 2850r / min, the high-precision mechanical slider drives the grinding head to slide up and down, and the front and rear electrode drive drives the grinding head to do reciprocating feeding motion. After polishing one side to a roughness of less than 1nm, repeat the above operation and polish the other side of the diamond film. After both sides of the diamond film are polished, the diamond film is placed in a mixed solution of concentrated sulfuric acid and concentrated nitric acid with a volume ratio of 1:1, heated in an electric furnace, and boiled for 30min~1h, wherein the concentration of concentrated sulfuric acid is 70%-98%, and the concentration of concentrated nitric acid is 65%~68%. Then the diamond film is placed in 100~200ml acetone, ethanol, and deionized water for ultrasonic cleaning, the frequency of the ultrasonic machine is 40kHz, and the ultrasonic time is 30min. Then take out the sample and blow dry the sample surface with nitrogen. After that, the diamond film was placed in a magnetron sputtering chamber, and sputtered at 25-400°C for 30min-1h and at 500-1500°C for 30min-1h alternately. The specific conditions were to adjust the Ar flow rate to 30-70sccm, the sputtering pressure to 1-3Pa, the sample stage speed to 3rpm, and the sputtering time to 30min-1h at each temperature. Thus, a highly oriented diamond anti-reflection film with slight hydrophobicity was obtained. Figure 2 The diagram of the stacked antireflection film is shown in FIG. Figure 4 Shown is the infrared transmittance spectrum of the diamond / erbium oxide composite material, which increases the highest point of diamond infrared transmittance from 58% to 73%.
Claims
1. A method for preparing a highly oriented hydrophobic oxide antireflection film for a diamond infrared window, wherein the growth rate of the antireflection film is regulated by regulating the temperature, thereby preparing a multilayer highly oriented oxide film on the surface of the diamond, and specifically comprising the following steps: Step 1: Diamond surface precision polishing Stick the diamond film on an automatic polishing machine and polish the diamond with a polishing disk until the diamond surface roughness is less than 1nm. Repeat the above steps and perform the same polishing treatment on the other side of the diamond film. Step 2: Acid boiling treatment of diamond surface The polished diamond film was acid-boiled to remove the metal debris and non-diamond phase remaining on the surface of the diamond film, and then ultrasonically cleaned in acetone, ethanol, and deionized water in sequence, and then dried; Step 3: Magnetron sputtering process The oxide target was mounted on the RF target, and then the cleaned diamond film was placed in the magnetron sputtering chamber, and the magnetron sputtering chamber was evacuated to a pressure of 1×10 -4 Pa~9×10 -4 Pa, introduce sputtering gas Ar, adjust the gas pressure to 1-3 Pa, adjust the substrate temperature between 25℃ and 1500℃, and the sample stage speed is 3-15rpm. The sputtering thickness is given by the formula d=λ 介 / 4 is determined to obtain the best anti-reflection effect, where λ 介 is the wavelength of light that needs to be transmitted in the anti-reflection film; thus, the preparation of a highly oriented anti-reflection film on the surface of the diamond film has been achieved.
2. The method for preparing a highly oriented hydrophobic oxide antireflection film for a diamond infrared window according to claim 1, characterized in that: In the step 1, the polishing process is carried out using an automatic polishing machine, the polishing disc speed is 2850r / min, the high-precision mechanical slider drives the grinding head to slide up and down, the front and rear electrode drives drive the grinding head to do forward and backward reciprocating feeding motion, the front and rear speeds are adjusted according to actual needs, and mechanical pressure is provided to make the diamond and the grinding disc frictionally grind. The automatic grinder has an adjustable pressure range of 100 to 1700N, the front and rear movement of the grinding head is 0 to 40mm, the grinding monitoring accuracy is 0.02mm, and the grinding flatness is ≤0.02mm.
3. The method for preparing a highly oriented hydrophobic oxide antireflection film for a diamond infrared window according to claim 1, characterized in that: In the step 2, the acid boiling is carried out by using a mixed acid of concentrated sulfuric acid and concentrated nitric acid in a volume ratio of 1:1, which is heated to boiling in an electric furnace, and the acid boiling time is 30 minutes to 1 hour, wherein the concentration of concentrated sulfuric acid is 70% to 98%, and the concentration of concentrated nitric acid is 65% to 68%.
4. The method for preparing a highly oriented hydrophobic oxide antireflection film for a diamond infrared window according to claim 1, characterized in that: In the step 2, the amount of acetone, ethanol and deionized water used is 100-200 ml, the frequency of the ultrasonic machine used is 40 kHz, and the ultrasonic time is 30 min. Then the sample is taken out and the surface of the sample is blown dry with nitrogen.
5. The method for preparing a highly oriented hydrophobic oxide antireflection film for a diamond infrared window according to claim 1, characterized in that: In the step three, the oxide composite target material used has a highly oriented crystal structure, and the target material is one or a combination of hafnium oxide, yttrium oxide, erbium oxide, and aluminum oxide.
6. The method for preparing a highly oriented hydrophobic oxide antireflection film for a diamond infrared window according to claim 1, characterized in that: In step 3, the antireflection film is prepared in a fast and slow manner, that is, low temperature and high temperature are performed alternately: sputtering at 25-400°C for 30min-1h, sputtering at 500-1500°C for 30min-1h, and the two are performed alternately until the sputtering thickness reaches d=λ 介 / 4.
Citation Information
Patent Citations
Oxide sintered body, oxide film obtained therefrom and transparent material containing it
CA2568966A1
Method for producing a composite pane with a corrosion-protected functional coating
CA2969290A1
Composite oxide sintered body and transparent conductive oxide film
CN104520467A
Diamond infrared composite window material and preparation method thereof
CN116555762A
Thin film thermistor forming method and manufacture of thin film thermistor element
JP1997092508A
Cited By
Preparation method of porous polyether-ether-ketone as guided bone regeneration barrier membrane
CN119427741A
A method for preparing porous polyetheretherketone as a barrier membrane for guided bone regeneration
CN119427741B